Model-based assessment of biomass incorporation to mitigate nitrogen losses from arable fields in Central Europe - Rothardt, Steffen; Kage, Henning (Frontiers in Agronomy, 2023)
Nitrogen (N) loss by leaching is a major concern in common crop rotations in Central Europe due to high post-harvest soil mineral N, low N uptake in autumn/winter, and percolation. This can lead to eutrophication of water bodies and indirect greenhouse gas emissions. One potential solution is to control microbial immobilization through the incorporation of organic matter. To examine the effectiveness of this approach, we compared the incorporation of crop residues from winter oilseed rape, faba beans, and winter wheat with the application of sawdust in a field-scale experiment. Field observations of the impact on autumn/winter N-dynamics were supplemented with model-derived parameters. Our results showed that the incorporation of crop residues significantly reduced autumn net mineralization in topsoil, with the largest reduction seen with cereal straw. However, the temporal dynamics of the effect did not meet the desired time frame, and the impact on N leaching was low. Field data, modeling processes, and a theoretical amendment assessment suggested that resistant organic matter accumulated under the given environmental conditions, probably resulting in a long-term effect on nutrient dynamics. In conclusion, incorporating crop residues from the preceding crop is the best option to date for mitigating post-harvest N losses and improving soil health with minimal crop management effort. However, controlling microbial immobilization through organic matter incorporation can be a useful measure whose effectiveness depends on the amendment used and field conditions.